The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/ajcp/aqy125
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Long-Term Model for Analysis and Improvement of Underfilled Blood Culture Volumes

Abstract: Partnering with a specific unit and providing monthly volume reports with educational sessions has a direct positive correlation on increasing ABCFVs. Increasing ABCFVs has the potential to decrease false-negative blood cultures, time to detection of positive blood cultures, and time to appropriate and specific antimicrobial therapy, as well as improve patient outcomes in high-acuity patient care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[16][17][18] Automated BC volume measurements have enabled largerscale feedback and education interventions across several healthcare systems showing reduced BC underfilling, in some cases associated with increased BC true positivity rate. [19][20][21] The incidence of solitary BC sets in the ED has been shown to range from 16.9% to >90% 9,22 and from a wider hospital perspective 48% to 94%. 23,24 Despite this, published interventions to reduce solitary BC are few.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Automated BC volume measurements have enabled largerscale feedback and education interventions across several healthcare systems showing reduced BC underfilling, in some cases associated with increased BC true positivity rate. [19][20][21] The incidence of solitary BC sets in the ED has been shown to range from 16.9% to >90% 9,22 and from a wider hospital perspective 48% to 94%. 23,24 Despite this, published interventions to reduce solitary BC are few.…”
Section: Discussionmentioning
confidence: 99%
“…Such monitoring easily highlights what preanalytical factor needs to be improved, and training (e.g. of nurse or phlebotomists) has thus become pivotal to improve, for example, bottle filling and the quality of skin preparation [14,15]. However, adequate filling may be moderate also in post-intervention assessments [15] and training effects may also fade with time, which calls for new strategies to reach effective training.…”
Section: Op Mize Treatmentmentioning
confidence: 99%
“…of nurse or phlebotomists) has thus become pivotal to improve, for example, bottle filling and the quality of skin preparation [14,15]. However, adequate filling may be moderate also in post-intervention assessments [15] and training effects may also fade with time, which calls for new strategies to reach effective training. Second, manufacturers have implemented technical features for automated estimation of the bottle filling in CMBCSs either with a direct or an indirect estimation of the amount of blood cultured (Table 2) [17,18].…”
Section: Op Mize Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One group found that targeted education in intensive care units (ICUs) led to 30% to 60% sustained improvement in blood volume submitted on average. 22 Another recent study found that a rigorous quality improvement program that included group education, targeted communications, and bottle marking led to not only considerably increased blood volume (increased from 2.3 mL average per bottle before implementation to 8.6 mL after implementation) but most importantly a 20% improved yield of true pathogens in blood culture. 23 …”
Section: Volume Of Blood Collected For Culturementioning
confidence: 99%